Conserving medicinal plants in Ghana - Owusu-Afriyie, George (Technical Centre for Agricultural and Rural Cooperation, 2005)
George Owusu-Afriyie describes how BG-BASE, a database program designed to manage information on botanical collections, is helping to conserve medicinal plants in Ghana.